Pengaruh Penggunaan Thermoelectric Cooler Terhadap Unjuk Kerja Kotak Pendingin Portable - Santika, I Gede Yoga Darma; Astika, I Made; Sucipta, I Made (Teknik Desain Mekanika, 2022)
Abstract Weather conditions and air temperature when traditional fishermen go to sea are often unpredictable. So that the freshness of the fish is not maintained because there is no good storage process. Along with technological developments at this time, a cooler that uses ice will be more effective if other cooling devices are added, for example by using a thermoelectric cooler (TEC) as a backup if the ice is no longer able to cool the fish. The procedure of this research was carried out by first putting 4 liters of water into an ice container and then putting it in the freezer for 24 hours after that it was put into a portable cooler box and then the temperature and humidity were measured. In the experiment without TEC, the air temperature that can be achieved in 40 minutes is 2.9 °C, while the air temperature that can be achieved by adding TEC is 2.6 °C. Within 900 minutes without TEC the temperature has reached 26.9 °C, but the experiment added with TEC is far below the temperature without TEC, which is 21.8 °C. In the trend of air humidity at the beginning of the experiment without TEC was 84.40% and for those added with TEC, namely 88.60% the humidity continued to increase along with melting ice in a portable cooler. In the experiment that was not added TEC at 900 minutes the humidity reached 88.70%, while in the experiment that added TEC the humidity at 1000 minutes was 93.40%. Keywords: cooler box portable, thermoelectric